2011
DOI: 10.1128/jcm.00756-10
|View full text |Cite
|
Sign up to set email alerts
|

Adenoid Reservoir for Pathogenic Biofilm Bacteria

Abstract: Biofilms of pathogenic bacteria are present on the middle ear mucosa of children with chronic otitis media (COM) and may contribute to the persistence of pathogens and the recalcitrance of COM to antibiotic treatment. Controlled studies indicate that adenoidectomy is effective in the treatment of COM, suggesting that the adenoids may act as a reservoir for COM pathogens. To investigate the bacterial community in the adenoid, samples were obtained from 35 children undergoing adenoidectomy for chronic OM or obst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
120
3
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(146 citation statements)
references
References 68 publications
10
120
3
10
Order By: Relevance
“…[17] Adenoidectomy is thought to remove the reservoir of pathogens that transiently colonize in the upper respiratory tract mucosa and contribute to the development of OM. [18] Recently, it has been suggested that chronic OM is associated with the persistence of bacterial pathogens in biofilms despite the use of antibiotics. This finding has been supported by animal studies.…”
Section: Adenoidectomy Indicationsmentioning
confidence: 99%
“…[17] Adenoidectomy is thought to remove the reservoir of pathogens that transiently colonize in the upper respiratory tract mucosa and contribute to the development of OM. [18] Recently, it has been suggested that chronic OM is associated with the persistence of bacterial pathogens in biofilms despite the use of antibiotics. This finding has been supported by animal studies.…”
Section: Adenoidectomy Indicationsmentioning
confidence: 99%
“…Колонізація па-тогенними бактеріями була виявлена в 57,5 % дітей із хронічним аденоїдитом одночасно із вторинним ураженням миготливого епітелію, що сприяє під-тримці хронічної запальної реакції [1]. Патогенні бактерії присутні на слизовій оболонці аденоїдів ді-тей із хронічним середнім отитом, сприяючи трива-лій персистенції збудників та стійкості до лікування антибіотиками [11]. У таких випадках видалення аденоїдів нерідко є неефективним і потребує по-вторних втручань [3].…”
Section: дослідження є фрагментом науково-дослідної роботи кафедри пеunclassified
“…Наиболее типичные представители бактериальных ассоциаций биопленок -Streptococcus pneumoniae, Staphylococcus aureus, Pseudomonas aeruginosa [13,14]. В исследованиях показано, что ассоциация этих бактерий играет одну из ключевых ролей в персистенции воспа-ления в носоглотке [15,16].…”
Section: оригинальная статьяunclassified